2023
DOI: 10.1097/yic.0000000000000476
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obsessive-compulsive symptoms and their psychosocial correlates among medical students during COVID-19 pandemic

Abstract: This study aimed to assess the prevalence of obsessive-compulsive symptoms (OCS) among medical students during COVID-19 pandemic and to evaluate their association with related sociodemographic features and other psychological symptoms. In this cross-sectional study, students from Mashhad University of Medical Sciences with no major exam in the preceding or following month were surveyed during April to August 2021 through stratified available sampling. Data were collected by a structured online questionnaire di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…COVID-19 pandemic indeed heavily influenced daily living of the general population, but medical students were particularly affected given the proximity to patients and the need of constant individual protection. It is not therefore surprising that in the data reported by Nahidi et al about one-third of the students showed obsessivecompulsive symptoms during pandemic (Nahidi et al, 2023). Interestingly, a trend of higher symptomatology was observed in subjects with history of COVID-19 infection, suggesting a sort of post-traumatic-like sequelae in those subjects.…”
mentioning
confidence: 86%
“…COVID-19 pandemic indeed heavily influenced daily living of the general population, but medical students were particularly affected given the proximity to patients and the need of constant individual protection. It is not therefore surprising that in the data reported by Nahidi et al about one-third of the students showed obsessivecompulsive symptoms during pandemic (Nahidi et al, 2023). Interestingly, a trend of higher symptomatology was observed in subjects with history of COVID-19 infection, suggesting a sort of post-traumatic-like sequelae in those subjects.…”
mentioning
confidence: 86%